The quality of material care provided by grandparents for their orphaned grandchildren in the context of HIV/AIDS and poverty: a study of Kopanong municipality, Free State - Tsiliso Tamasane; Judith Head (Taylor & Francis Group, 2010)
A pervasive argument in the literature on AIDS orphans in South Africa is that grandparents, who often care for their orphaned grandchildren, lack the material means to provide adequate care. This study investigated that claim in an area of ubiquitous poverty and very high unemployment. It is based on the analysis of data obtained from two surveys carried out by the HSRC in the semi-rural municipality of Kopanong in the Free State. The first study was a census which targeted the whole population. The second, smaller survey sampled households which accommodated orphaned and vulnerable children. Based on four proxy indicators for material care: possession of birth certificates, uptake of welfare grants, levels of school attendance, and the number of meals consumed daily, the study revealed that there was very little difference in the quality of care provided by grandparents and other carers, including biological parents. Indeed, since the old age pension is much higher than the child support grant and the foster care grant it may be that grandparents who are pensioners generally have higher incomes than most other adults. In line with the findings of other research, the study found that poverty is a major problem confronting all carers in the area. It concludes that interventions that primarily target orphans overlook the material needs of all poor children. It therefore joins the calls of other researchers for greater state support for all poor children, irrespective of whether they are orphans and who their carers are.